Harlequin Foetus - Basu Kaberi; Datta Pijush; Das Pradip K (Wolters Kluwer Medknow Publications, 1997)
The clinical and histopathological features of a male harlequin foetus born to a consanguineous couple is described. Routine laboratory investigations were within normal limits. The neonate, who was treated symptomatically, died on the 4th day principally due to lung compromise